Pengaruh Ukuran Perusahaan, Umur Perusahan, Rofitabilitas, Leverage, Dan Pertumbuhan Penjualan Terhadap Tax Avoidance Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2020 - Aida Fitri Nasution; Tuti Anggraini; Arnida Wahyuni Lubis (LPPM Universitas Labuhanbatu, 2022)
This research will explore the impact of firm size, firm age, profitability, leverage, and sales growth on tax avoidance in food and beverage manufacturing companies listed on the Indonesian stock exchange in 2017-2020. This research is a quantitative research that uses secondary data in the form of financial reports which are accessed through www.idx.ac.id. The research population was 30 manufacturing companies in the food and beverage sector and the research sample was 14 companies obtained using the purposive sampling method for 4 years so that the number of samples was 56 observational data. The data analysis technique used is panel data regression analysis with Fixed Effect Model estimation which is tested using Eviews 9. The results show that, firstly, firm size has no effect on tax avoidance so that Companies with high or low total assets have not been able to guarantee that the company will take tax avoidance actions or not. Both, firm age have an effect on tax avoidance this means that companies that experience aging and have long operational times have experience in carrying out tax avoidance actions, so that company size can influence companies to take tax avoidance actions. Third, profitability has no effect on tax avoidance this means that companies that have high or low profitability cannot guarantee that profit before tax causes companies to take tax avoidance actions or not. The four, leverages have no effect on tax avoidance, this means that high or low debt both have high risks, so companies will tend to avoid other major risks to avoid taxes. The five, sales growth has an effect on tax avoidance, this means that the size of the company's sales level will increase the company's profit or profit, so that the tax to be imposed will also increase, therefore the company will tend to take tax avoidance actions. The six, company sizes, company age, profitability, leverage, and sales growth simultaneously affect tax avoidance, So that together, Â high or low independent variables can influence companies to take tax avoidance actions.